Investigating the effect of flue gas temperature and excess air coefficient on the size distribution of condensable particulate matters. (15th August 2021) - Peng, Yue; Shi, Nan; Wang, Tao; Wang, Jiawei; Zhang, Yongsheng; Chen, Wei-Yin; Sajjadi, Baharak; Pan, Wei-Ping
Highlights: A new test method was developed to obtain particle size distribution of CPM. Total mass of CPM increased with sampling temperature and excess air coefficient. Heterogeneous condensation was responsible for the whole range of particles in CPM. Homogeneous condensation leaded to the increase of finer particles. Abstract: Primary particles emitted from fuel combustion mainly involve filterable particulate matter (FPM) and condensable particulate matter (CPM). Particularly, CPM has emerged as a subject for further emission control. This study investigated the effects of the sampling temperature and excess air coefficient (EAC) on the total mass, chemical speciation, and particle size distribution of CPM by integrating Electrical Low-Pressure Impactor + (ELPI + ) sampling devices with the EPA Method 202 (dry impinger method). The total mass of CPM increased with the sampling temperature and EAC. Specifically, the total concentration of CPM was 10.51–39.93 mg/m 3, in which the mass fraction of organic species varied between 8.74 and 49.80%, and the organic components in CPM followed the ranking order of alkanes/alkenes (62.6–78.6%), oxygen-containing volatile organic compounds (OVOCs) (19.7–35.4%), and aromatics (5.6%). Compared with other inorganic species such as HCl and NOX, SO3 had a higher migration tendency from the flue gas to CPM. The particle size distribution suggested that heterogeneous condensation was responsible for the whole size range of particles in CPM, whereas the homogeneous condensation led to the increase of finer particles (smaller than 0.2 µm). Accordingly, adjusting the emission temperature and EAC could help to control the emission of CPM.